Garra rezai, a new species from two widely disjunct areas in the Tigris drainage (Teleostei: Cyprinidae) - Mousavi-Sabet, Hamed; Eagderi, Soheil; Saemi-Komsari, Maryam; Kaya, Cüneyt; Freyhof, Jörg (Zootaxa, 2022)
Garra rezai, new species, is described from the Chooman, a tributary of the Lesser Zab in Iran, and from headwaters of the Yanarsu, a tributary of the upper Tigris in Turkey. It is distinguished from its congeners in the Garra variabilis species group by having two pairs of barbels, a well-developed mental disc, 35–40 total scales along the lateral line, 15–19 scales along the predorsal midline, and 15–18 circumpeduncular scales. It is further characterised by having ten diagnostic nucleotide substitutions and the K2P genetic distances with the closest species i.e. G. klatti, G. kemali and G. variabilis as 11.9, 12.0, and 13.7%, respectively in the mtDNA COI barcode region.